Images as Information: Context-Rich Images and the Communication of Place-Based Information Through Increased Representation in Environmental Governance - Curry, Tracie; Lopez, Ellen D. S. (Frontiers in Communication, 2020)
Practitioners widely acknowledge the importance of including local and Indigenous knowledge in environmental research and decision-making. Nevertheless, it remains a challenge to achieve this integration in a meaningful way. The pilot study reported here was a necessary step toward developing improved methods for communicating local and Indigenous knowledge to decision-makers, with a focus on public sector practitioners as audience and visual content as medium. The proposed methodology extends previous research on climate change adaptation in the Alaskan Arctic, and it examines the effect of a reporting approach that introduces two components outside of general conventions in public sector information dissemination; 1) the application of context-rich images to help convey the social and cultural nuances of place-based information, and 2) multiple evidence base (MEB) reporting which engages information from both Western science and local/Indigenous knowledge systems. Context-rich images  defined here as detailed visuals that address the particularities of specific environments and cultures – are explored given their potential merits in expressing place-based concepts, such as social life and lived experience quickly and concisely when presented in tandem with text. With a focus on practical application, public sector conventions for reporting place-based information to decision-makers are investigated, including the benefits and limitations associated with these conventions. Insights from both theory and practice informed the research methodology, and the design of a sample report and online questionnaire tested with upper-level public sector practitioners who have influence on environmental decision-making. Pilot study results indicated significant benefits of using context-rich images in addition to quotes about lived experience for reporting information about the local context and experience of Northern environmental changes. When presented alongside research from Western science, neither local observations in the form of quotes, nor context-rich images posed negative impacts on the perceived credibility of the report. The pilot study revealed the proposed methodology to be particularly beneficial for a target audience of practitioners who may lack expertise in the local context or field of research being reported. Additionally, several potential improvements to the content and design of research materials were identified for the benefit of future studies.